Lifting the US crude oil export ban: A numerical partial-equilibrium analysis - Lissy Langer; Daniel Huppmann; Franziska Holz (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The upheaval in global crude oil markets and the boom in oil production from shale plays in North America have brought scrutiny on the export ban for crude oil in the United States. This paper examines the global flows and strategic refinery adjustments in a spatial, game-theoretic partial-equilibrium model. We consider de- tailed supply chain infrastructure with multiple crude oil qualities (supply), distinct oil products (demand), as well as specific refinery configurations and modes of transport (mid-stream). Investments in production capacity and infrastructure are endogenous. We compare two development pathways for the global oil market: one projection retaining the US export ban, and a counterfactual scenario lifting the export restrictions. Lifting the US crude ban, we find significant expansion of US sweet crude exports. In the US refinery sector, more heavy sour crude is imported and transformed. While US producers gain, the profits of US refiners decrease, due to reduced market distortions and a more efficient resource allocation. Countries importing US sweet crude benefit from higher product output, while avoiding costly refinery investments. Producers of heavy sour crude (e.g. the Middle East) are incentivised to climb up the value chain to defend their market share and maintain their dominant position.
Keywords: Q41; Q47; Q48; C61; 330; energy system model; crude oil market; US crude export ban; refining capacity; infrastructure investment